2014
DOI: 10.13171/mjc.3.4.2014.09.07.11
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, antibacterial and antioxidant activities of Tunisian garlic (Allium sativum) essential oil and ethanol extract

Abstract:  The aim of the study is to establish some nutritional properties of garlic cultivated in Tunisia and to evaluate the antioxidant and the antimicrobial activites of its essential oil and ethanol extract. Tunisian garlic (Allium sativum) was characterized for moisture, ash and protein contents which were determined as 66%, 1.4% and 5.2% respectively. In addition, Fe (5.90 mg/kg), Cu (1.61 mg/kg), Mg (15 mg/kg) and P (140 mg/kg) were reported such as the major minerals in garlic. The fat profile of tunisian gar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 3 publications
3
11
0
Order By: Relevance
“…In other studied varieties of garlic higher total polyphenols content was found in the area of Nitra. Chekki et al (2014) indicated, that the total polyphenols content in garlic is in the wide range from 436 mg kg -1 to 645 mg kg -1 , which good correlate with the results of this work. Some authors reported even a higher value of TPC in garlic: 812 mg kg -1 (Charles, 2013), 1290 mg kg -1 (Wangcharoen & Morasuk, 2009).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In other studied varieties of garlic higher total polyphenols content was found in the area of Nitra. Chekki et al (2014) indicated, that the total polyphenols content in garlic is in the wide range from 436 mg kg -1 to 645 mg kg -1 , which good correlate with the results of this work. Some authors reported even a higher value of TPC in garlic: 812 mg kg -1 (Charles, 2013), 1290 mg kg -1 (Wangcharoen & Morasuk, 2009).…”
Section: Resultssupporting
confidence: 90%
“…The coefficient of correlation (r = 0.9315 -0.9978) confirmed strong dependency between the content of polyphenols, total sulfur content and the antioxidant activity and the results are in good agreement with the findings of Mahmutović et al (2014), who confirmed correlations between total polyphenols content, total sulfur content and antioxidant activity in garlic. Ramkissoon et al (2012), Chekki et al (2014) indicated correlations between total polyphenols content and antioxidant activity in garlic, onion and other vegetable..…”
Section: Bardejovmentioning
confidence: 97%
“…In comparison with this study Batcioglu et al (2012) indicated lower total polyphenol content in garlic is 780 mg*kg -1 , similarly Charles (2013) recorded that TPC in garlic is 812 mg*kg -1 . Some authors reported even a lower value of TPC in garlic: 436 mg*kg -1 (Chekki et al, 2014), 410 mg*kg -1 (Wangcharoen and Morasuk, 2007), 493 mg*kg -1 (Jastrzebski et al, 2007). By way of contrast Wangcharoen and Morasuk (2009) The values of antioxidant activity in the studied samples are presented in Table 3.…”
Section: Resultsmentioning
confidence: 86%
“…Besides, allicin is a typical reactive sulfur species found in the essential oil. 5 Recently, many people have been infected with a novel coronavirus (SARS-CoV-2), and the death toll has reached thousands and been increasing day by day, which is a major problem in the world. 6 Therefore, the demand to seek for natural and safe medicines to prevent coronavirus is of great concern for all scientists around the world.…”
Section: Introductionmentioning
confidence: 99%